Guidelines for using Information Technology in Accounting to Maximize the Efficiency of Organizations in the Industrial Business Sector - Kamolprem, Bongkoch; Lata, Pannarai; Silpcharu, Thanin (Migration Letters, 2023)
This research aims to study the approach of using information technology in accounting for the maximum efficiency of organizations in the industrial business sector and to develop it into a structural equation model. The qualitative research used in-depth interviews and group discussions for model validation. For the quantitative research, a survey was conducted with executives in the accounting sector of the industrial business, totaling 500 entities. The statistical values used include descriptive statistics, inferential statistics, and multivariate statistics. The research findings indicate that the approach to using information technology in accounting for the maximum efficiency of organizations in the industrial business sector comprises five aspects as follows: 1)Strategic Analysis (X ̅ = 4.32 2)Risk Management (X ̅ = 4.31) 3)Forecasting (X ̅ = 4.25) 4) Business Intelligence (X ̅ = 4.17) And 5) Information Generation (X ̅ = 4.12) The hypothesis testing results revealed that medium-sized and small businesses differ significantly from large businesses. The analysis of the developed structural equation model showed that it meets the evaluation criteria. It is consistent and coherent with empirical data, with the probability value of Chi-square, the relative Chi-square value, the goodness-of-fit index, and the root mean square error of approximation being 0.057, 1.140, 0.954, and 0.017, respectively.